Strategic Recommedation on Consumer Financing Business Center (CFBC) a Part of Consumer Banking Division PT Bank Syariah Mandiri - Setiawan, Ari Ervan; Jayaprawira, Acep R (The Indonesian Journal of Business Administration, 2013)
The position of consumer financing PT Bank Syariah Mandiri (BSM) until the end of 2011 reached Rp16 trillion, where achievement is increased by 58.23% compared to the end of 2010. An increasing number of consumer financing is also accompanied by another achievements namely stable value of NPF. Management target consumer financing in 2015 amounted to Rp50 trillion. This journal is to formulate a strategy for Consumer Finance Division, particularly in the business unit Consumer Financing Business Center (CFBC). The strategy formulated by external analysis through STEEP (Sociocultural, Technological, Economic, Ecological, And Political-Legal Environmental Forces); industry analysis porter five-force, and industry matrix. While an internal analysis conducted by analysis of quality of service, with a SWOT analysis to know the root of the problem. The results of the external and internal aspects of SWOT then summarized in SFAS (Strategic Factor Analysis Summary). Strategy formulation derived from the TOWS matrix. SWOT analysis showed Consumer Finance Division is in the area grow and build with alternative strategies include intensive strategy (market penetration, market development, and product development) or integration strategies (backward integration, forward integration, and horizontal integration). Effort needs to be done is to optimize the acquisition of CFBC application from Development Cooperation by way of making a scheduled visit of CFE (Consumer Financing Executive) that are always monitored directly by CSM (Consumer Sales Manager). Implement a comprehensive B2B collaboration to potential developers. Optimizing referrals from the branch, propose to the Consumer Finance Division that branches provide referral incentives on KPI (Key Performance Indicator), so that the branches are encouraged to approach the developers. Create and develop talent management. Increase promotion through various media and several ways.Ã‚Â Keywords : Islamic banking, consumer finance, CFBC, grow and build, strategy.